Assessment of biomarkers in women with endometriosis-associated pain using the ENG contraceptive implant or the 52 mg LNG-IUS: a non-inferiority randomised clinical trial. (3rd September 2018) - Margatho, Deborah; Mota Carvalho, Nelsilene; Eloy, Larissa; Bahamondes, Luis
Abstract: Objective: The aim of the study was to assess the serum levels of the following biomarkers in women with endometriosis-associated pelvic pain before and after six months of using the etonogestrel (ENG) contraceptive implant or the 52 mg levonorgestrel-releasing intrauterine system (LNG-IUS): cancer antigen (CA)-125, cluster of differentiation (CD) 23 and endometrial nerve fibre density. Methods: The study was conducted at the Department of Obstetrics and Gynaecology, University of Campinas Medical School, Brazil. A total of 103 women with endometriosis-associated pain diagnosed by surgery, transvaginal ultrasound and/or magnetic resonance imaging were included. Endometrial nerve fibre density and serum levels of CA-125 and soluble CD23 were assessed before and after six months of using the allocated method and were correlated to 10 cm visual analogue scale (VAS) scores for non-cyclical pelvic pain and dysmenorrhoea. Results: Both contraceptive methods significantly reduced concentrations of serum soluble CD23 and endometrial nerve fibre density ( p  < .001); however, CA-125 was significantly reduced only among users of the ENG implant ( p  < .05). No correlation was observed between reduction of biomarkers and improvement of VAS pain and dysmenorrhoea scores. No differences were observed between the ENG implant and the LNG-IUS. Conclusion: Both progestin-only contraceptives significantly reduced two out of the three biomarkers evaluated. These two biomarkers could, therefore, be used as surrogate markers to follow up medical treatment of endometriosis-associated pain.